Epidemiologic Methods (De Gruyter, 2011)
Epidemiologic Methods is devoted entirely to methodology in the field of epidemiology. The journal aims to bring novel methodology more quickly to the epidemiologic community and to provide a forum for longer or more technical papers on epidemiologic methods. It serves as a repository of methodologic contributions focused on advancing and improving epidemiologic analysis.